Keratin 6A promotes skin inflammation through JAK1-STAT3 activation in keratinocytes - Mengting Chen; Yaling Wang; Mei Wang; San Xu; Zixin Tan; Yisheng Cai; Xin Xiao; Ben Wang; Zhili Deng; Ji Li (Journal of Biomedical Science)
Abstract Background Skin barrier dysfunction and immune activation are hallmarks of inflammatory skin diseases such as rosacea and psoriasis, suggesting shared pathogenic mechanisms. While barrier disruption may trigger or exacerbate skin inflammation, the precise underlying mechanisms remain unclear. Notably, epidermal barrier compromise leads to a marked increase in barrier alarmin expression. Among these, keratin 6A (KRT6A) plays a role in maintaining skin barrier integrity. Methods We treated mouse skin and human keratinocytes, with and without KRT6A expression, with LL37/TNF-α and assessed the severity of inflammation. The specific mechanism by which KRT6A promotes skin inflammation was investigated using mass spectrometry and immunoprecipitation assays. Results KRT6A expression was elevated in lesional skin from patients and mouse models of rosacea and psoriasis. In mice with LL37-induced rosacea-like and imiquimod (IMQ)-induced psoriasis-like skin inflammation, KRT6A knockdown alleviated inflammation, whereas KRT6A overexpression exacerbated inflammatory responses. Mechanistically, KRT6A activated signal transducer and activator of transcription 3 (STAT3) and enhanced proinflammatory cytokine expression in keratinocytes by reducing Janus kinase 1 (JAK1) ubiquitination. This occurred through inhibition of ring finger protein 41 (RNF41)-mediated JAK1 binding. Conclusions Our findings indicate that KRT6A expression increases following epidermal barrier disruption and contributes to exacerbated skin inflammation in disease conditions. Targeting KRT6A may represent a novel therapeutic approach for inflammatory skin diseases associated with epidermal dysfunction.